2013
DOI: 10.1051/0004-6361/201220976
|View full text |Cite
|
Sign up to set email alerts
|

Water in star-forming regions withHerschel(WISH)

Abstract: Context. Water is a key constituent of star-forming matter, but the origin of its line emission and absorption during high-mass star formation is not well understood. Aims. We study the velocity profiles of low-excitation H 2 O lines toward 19 high-mass star-forming regions and search for trends with luminosity, mass, and evolutionary stage. Methods. We decompose high-resolution Herschel-HIFI line spectra near 990, 1110 and 1670 GHz into three distinct physical components. Dense cores (protostellar envelopes) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 88 publications
(60 reference statements)
7
81
1
Order By: Relevance
“…3.2) is similar to that of Kristensen et al (2012) toward lowmass protostars, and to the description of the H 2 O profiles of van der Tak et al (2013) toward high-mass protostars. Herpin et al (2012) found a similar profile decomposition toward the massive protostar W43-MM1.…”
Section: Gas Kinematicssupporting
confidence: 78%
See 3 more Smart Citations
“…3.2) is similar to that of Kristensen et al (2012) toward lowmass protostars, and to the description of the H 2 O profiles of van der Tak et al (2013) toward high-mass protostars. Herpin et al (2012) found a similar profile decomposition toward the massive protostar W43-MM1.…”
Section: Gas Kinematicssupporting
confidence: 78%
“…Our estimated values of σ are consistent with those found by Hajigholi et al (2015) toward G34.3+0.15. Some of the high-mass protostars studied by van der Tak et al (2013) also show regular and inverse P-Cygni profiles, but they do not analyze the line profiles and thus we cannot directly compare our results. Instead, we can compare our results with those of Herpin et al (2012) toward the massive protostar W43-MM1, where they derive infall velocities as high as 2.9 km s −1 and turbulent velocities > ∼ 2 km s −1 .…”
Section: Sourcementioning
confidence: 94%
See 2 more Smart Citations
“…We therefore prefer to use terms which indicate the most likely physical origin of the emission component (cf. van der Tak et al 2013, for similar terminology applied to high-mass protostars). Table 3 provides a summary of how these new terms are related to those used in previous papers on low-mass protostars in order to ensure continuity.…”
Section: Gaussian Decompositionmentioning
confidence: 99%